KRITIK SHAá¸¤RUR TERHADAP KONSEP SUNNAH - Iswahyudi, Iswahyudi (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
Sha?rûr methodology and legal implications have been widely written by researchers, but only some researchers elaborate Sunnah in depth analysis. In discussing Sunnah, Sha?rûr mentioned the problems that have serious implications, such, whether all the words, actions and silence of Muhammad is the result of revelation or ijtihâd of Muhammad himself? Sha?rûr assumed that Sunnah is actually the result of ijtihâd of Muhammad himself and it is not revelation. Therefore, definition that has been established on Sunnah (everything that comes from Muhammad either of the words, deeds and statutes) is not appropriate. Dissolving this definition for Sha?rûr became possible because these definitions are not made by Muhammad himself, but by the next generations. According to him, Sunnah is derived from the word sanna which means the ease and flow smoothly. Thus, what is said, done and set by Muhammad is an example of how such limits practiced in space and time of Muhammad. He is not the last and not the only laws that must be done. Based on the definition that has been made, Sha?rûr divided Sunnah into two categories, namely sunnah risâlah and sunnah nubûwah. Sunnah risâlah maintains on law, morals, and good manners, while sunnah nabûwah preserves objective sciences. Further, it implies that the adherence to sunnah risâlah is an obligation, adherence to sunnah nubûwah is non-compulsory.